DISCOURSE ON THE DEGRADATION OF THE AUTHENTICITY OF THE SOGAN DIALECT OF THE BALI LANGUAGE - I Komang Sukayasa, (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
The socio-cultural order cannot be said to be authentic when the cultural acculturation process occurs. When the Songan people are so confident in their authenticity that they call themselves the Bali Aga people, they sometimes forget that their social order is no longer authentic. This research is motivated by three problems, first, what form does the discussion of the degradation of the Balinese Songan dialect take? second, what is the process of degradation of the authenticity of the Balinese Songan dialect; third, what forces the degradation of the authenticity of the Balinese Songan dialect on the social order of the Songan community. The type of data in this research is qualitative data, namely in the form of words and expressions related to discussions regarding the degradation of the authenticity of the Balinese Songan dialect. The data sources in this research are primary data and secondary data. Data collection techniques are interviews, observation and document study. Data analysis techniques are carried out by identifying data, clarifying data, and interpreting. The theory used in this research is sociolinguistic theory to discuss the first problem, globalization theory to discuss the second problem, praxis theory to discuss the third problem. The results of this research indicate that the form of Balinese language discourse in the Songan dialect occurs in the family and traditional domains. The lack of a place for dialect use in the family and customary realm is the cause. The process of discourse on the degradation of the Balinese Songan dialect began with globalization and modernity, an unsupportive language environment, and the variety of dialects seen from the professions of the Songan village community. The implications of the degradation of the Songan dialect of Balinese include a decline in social order, social conflict and a decline in local identity